Human Retinal Pigment Epithelium Cells as Functional Models for the RPE In Vivo - Ablonczy, Zsolt (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. The two most commonly used in vitro models of the retinal pigment epithelium (RPE) are fetal human RPE (fhRPE) and ARPE-19 cells; however, studies of their barrier properties have produced contradictory results. To compare their utility as RPE models, their morphologic and functional characteristics were analyzed. METHODS. Monolayers of both cell types were grown on permeable membrane filters. Barrier function and cellular morphology were assessed by transepithelial resistance (TER) measurements and immunohistochemistry. Protein expression was evaluated by immunoblotting and ELISA assays, and retinoid metabolism characterized by HPLC. RESULTS. Both cultures developed tight junctions. However, only the fhRPE cells were pigmented, uniform in size and shape, expressed high levels of RPE markers, metabolized all-trans retinal, and developed high TER (>400 Ωcm(2)). The net secretion of pigment-epithelium-derived factor (PEDF) was directed apically in both cultures, but fhRPE cells exhibited secretion rates a thousand-fold greater than in ARPE-19 cells. The net secretion of vascular endothelial growth factor (VEGF) was significantly higher in fhRPE cultures and the direction of this secretion was basolateral; while net secretion was apical in ARPE-19 cells. In fresh media, VEGF-E reduced TER in both cultures; however, in conditioned media fhRPE cells did not respond to VEGF-E administration, but retreatment of the conditioned media with anti-PEDF antibodies allowed fhRPE cells to fully respond to VEGF-E. CONCLUSIONS. Properties of fhRPE cells align with a functionally normal RPE in vivo, while ARPE-19 cells resemble a pathologic or aged RPE. These results suggest a utility for both cell types in understanding distinct, particular aspects of RPE function.